Efeito das lâminas espectrais sobre desempenho da leitura em escolares do ensino fundamental - Garcia, Ana Carla Oliveira (2016)
Introduction:This study investigated the effects of using colored overlays on reading rate to improve reading for children.Objective: To investigate the effect of the use of colored overlays on reading achievement. Materials and Methods: The sample consisted of 68 children (9-12 years of age, 53% male) regularly enrolled in the 5th (n = 24) and 6 years (n = 44) of elementary school. Were included in this study all children without peripheral visual or hearing loss. Instruments: Reading Test(TELVER) and Irlen Reading Perceptual Scale (IRPS): through a variety of tasks that enhance the visual stress, the instrument was used to define the optimal spectral blade (Irlen overlays) for each individual. Results: 68 students analyzed in this study, 31% showed an improvement of at least 5% on reading speed after using the overlay. Among these patients with improvement, there was an average gain of 14% in speed reading. Only 2 patients had 25% gains with the use of the intervention (28.8% and 30.8%). There was no difference in the performance of TELVER between female and male before the intervention (t (1,66) = 1.37; p = 0.174), with spectral blades (t (1,66) = 1.13; p = 0.262), and the read gain (t (1,66) = 0.53, p = 0.598). Conclusion: These data are very close to the international literature that evaluated childrenin the general population, providing external validation for TELVER